Urticaria as the First Presentation of COVID-19 Infection - Suzan Sanavi (International Journal of Medical Practitioners, 2021)
A case report describes urticaria as an initial manifestation of COVID‑19. It outlines clinical course, differential diagnosis, and implications for testing and isolation.
Keywords: COVID-19